Learning Outcomes in Aqidah Akhlaq: Analysis of Quality and Implementation - Anwar, Adnan Nuril; Saputra, Bayu (Interdisciplinary Journal of Social Science and Education (IJSSE), 2025)
Aqidah Akhlak learning in Madrasah plays a strategic role in shaping students' character and personality, aligning them with Islamic values. One key indicator of the success of this learning process is the quality of the material received and understood by students. This article aims to analyze the quality of Aqidah Akhlak material by reviewing aspects of planning, implementation, and student learning outcomes. The research employs a descriptive qualitative method, with data collection techniques such as observation, interviews, and documentation. The research findings suggest that while the overall quality of Aqidah Akhlak material outcomes is satisfactory, there are still some challenges in the implementation process, particularly concerning the use of learning media and methods of delivery. In order to address these challenges, innovative strategies are required. Such strategies would not only enhance the effectiveness of the curriculum but also make the Aqidah Akhlak content more accessible and easier for students to understand and apply in their everyday lives.